2022
DOI: 10.1093/humrep/deac003
|View full text |Cite
|
Sign up to set email alerts
|

Impact of uterine malformations on pregnancy and neonatal outcomes of IVF/ICSI–frozen embryo transfer

Abstract: STUDY QUESTION What is the impact of uterine malformations on reproductive and neonatal outcomes of IVF/ICSI–frozen embryo transfer? SUMMARY ANSWER Unification defective uteri are associated with poorer neonatal outcomes including higher preterm delivery rate and lower birthweight, and septate uteri are associated with worse fertility outcomes including higher miscarriage and lower live birth rates (LBRs). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…The inconsistencies in the findings of the various studies in terms of perinatal outcomes may be caused by differences in inclusion and exclusion criteria, categories used to group blastocyst quality, and sample size distributions, especially the proportion of good-quality blastocysts in D6, as well as the relative subjectivity of blastocyst scoring. Pregnancy complications ( 31 ), uterine malformations ( 32 ), frozen-thawed technology ( 3 ), and different development rates from day 5 and day 6 ( 33 ), and the above-mentioned factors would all impact perinatal outcomes, including PTD. Meanwhile, another study ( 34 ) confirmed that an elevated AMH level would be an independent risk factor for PTD in overweight patients with polycystic ovary syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…The inconsistencies in the findings of the various studies in terms of perinatal outcomes may be caused by differences in inclusion and exclusion criteria, categories used to group blastocyst quality, and sample size distributions, especially the proportion of good-quality blastocysts in D6, as well as the relative subjectivity of blastocyst scoring. Pregnancy complications ( 31 ), uterine malformations ( 32 ), frozen-thawed technology ( 3 ), and different development rates from day 5 and day 6 ( 33 ), and the above-mentioned factors would all impact perinatal outcomes, including PTD. Meanwhile, another study ( 34 ) confirmed that an elevated AMH level would be an independent risk factor for PTD in overweight patients with polycystic ovary syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Our study found that high maternal age, primary infertility, low FSH level, and hormone replacement therapy (HRT) method of endometrial preparation for FET have a certain predictive value for preterm birth, while low FSH level, and HRT method of endometrial preparation for FET have a certain predictive value for low birth weight. In addition, other studies have found that other factors are associated with higher risks of preterm birth and low birth weight after FET, such as thin endometrium, 57 polycystic ovary syndrome (PCOS), 58 number of embryos transferred, 46 uterine malformation, 59 and higher estradiol level. 60 The value of multi-factor combination in predicting preterm birth and low birth weight is better than that of independent factors, which deserves our close attention.…”
Section: Discussionmentioning
confidence: 99%
“…International Journal of General Medicine 2022:15 endometrium, 57 polycystic ovary syndrome (PCOS), 58 number of embryos transferred, 46 uterine malformation, 59 and higher estradiol level. 60 The value of multi-factor combination in predicting preterm birth and low birth weight is better than that of independent factors, which deserves our close attention.…”
Section: Dovepressmentioning
confidence: 99%
“…Most studies have focused on only a particular type of uterine anomaly [ 7 9 ]. A retrospective study did rigorous work, but they focused solely on the frozen thawed embryo transfer (FET) outcomes of uterine anomaly [ 10 ], while the systematic study of fresh embryo transfer (IVF-ET) outcomes has not been studied.…”
Section: Introductionmentioning
confidence: 99%